Assessment of coronary calcification using calibrated mass score with two different multidetector computed tomography scanners in the Copenhagen General Population Study. Issue 88 (March 2017) - Fuchs, Andreas; Groen, Jaap M.; Arnold, Ben A.; Nikolovski, Sasho; Knudsen, Andreas D.; Kühl, J. Tobias; Nordestgaard, Børge G.; Greuter, Marcel J.W.; Kofoed, Klaus F.
Abstract: Objective: Population studies have shown coronary calcium score to improve risk stratification in subjects suspected for cardiovascular disease. The aim of this work was to assess the validity of multidetector computed tomography (MDCT) for measurement of calibrated mass scores (MS) in a phantom study, and to investigate inter-scanner variability for MS and Agaston score (AS) recorded in a population study on two different high-end MDCT scanners. Materials and methods: A calcium phantom was scanned by a first (A) and second (B) generation 320-MDCT. MS was measured for each calcium deposit from repeated measurements in each scanner and compared to known physical phantom mass. Random samples of human subjects from the Copenhagen General Population Study were scanned with scanner A (N = 254) and scanner B (N = 253) where MS and AS distributions of these two groups were compared. Results: The mean total MS of the phantom was 32.9 ± 0.8 mg and 33.1 ± 0.9 mg (p = 0.43) assessed by scanner A and B respectively – the physical calcium mass was 34.0 mg. Correlation between measured MS and physical calcium mass was R 2 = 0.99 in both scanners. In the population study the median total MS was 16.8 mg (interquartile range (IQR): 3.5–81.1) and 15.8 mg (IQR: 3.8–63.4) in scanner A and B (p = 0.88). The corresponding median total AS were 92 (IQR: 23–471) and 89 (IQR: 40–384) (p = 0.64). Conclusion: Calibrated calcium mass score may be assessed with very high accuracy in a calcium phantom by different generations of 320-MDCT scanners. In population studies, it appears acceptable to pool calcium scores acquired on different 320-MDCT scanners.